Terminal Deuterium Atoms Protect Silicon from Oxidation - Li, Tiexin; Peiris, Chandramalika; Aragonès, A.C.; Hurtado, Carlos; Kicic, Anthony; Ciampi, Simone; MacGregor, M.; Darwish, T.; Darwish, Nadim (2023)
In recent years, the hybrid silicon-molecular electronics technology has been gaining significant attention for applications in sensors, photovoltaics, power generation, and molecular electronics devices. However, Si-H surfaces, which are the platforms on which these devices are formed, are prone to oxidation, compromising the mechanical and electronic stability of the devices. Here, we show that when hydrogen is replaced by deuterium, the Si-D surface becomes significantly more resistant to oxidation when either positive or negative voltages are applied to the Si surface. Si-D surfaces are more resistant to oxidation, and their current-voltage characteristics are more stable than those measured on Si-H surfaces. At positive voltages, the Si-D stability appears to be related to the flat band potential of Si-D being more positive compared to Si-H surfaces, making Si-D surfaces less attractive to oxidizing OH- ions. The limited oxidation of Si-D surfaces at negative potentials is interpreted by the frequencies of the Si-D bending modes being coupled to that of the bulk Si surface phonon modes, which would make the duration of the Si-D excited vibrational state significantly less than that of Si-H. The strong surface isotope effect has implications in the design of silicon-based sensing, molecular electronics, and power-generation devices and the interpretation of charge transfer across them.